Digitalisasi UMKM Melalui Literasi Digital dan Digital Marketing Dalam Meningkatkan Kualitas Produk dan Volume Penjualan - Kader, Mukhtar Abdul; Prawiranegara, Benny; Setiawan, Reza Ananda Pahlevi; Shelyanti, Adel; Pratama, M. Bintang Yudha (Journal of Community Development, 2024)
The development of technology today has shown extraordinary progress but is not followed by the competence of its people, especially in rural areas. Many things in the field of life have utilized the existence of technology itself. The development of advanced technology is very rapid today, one of which is in the economic sector, namely digital marketing. Micro, Small and Medium Enterprises (MSMEs) are one of the pillars of the Indonesian economy and the strength of the regional economy that is currently intensively utilizing digital marketing in promoting their businesses. This community service activity was carried out in the Sukasetia Village area, where most of the residents have their own MSME products. However, its residents have not been able to utilize existing digital marketing technology properly in developing their businesses. Digitalization of MSMEs today where a necessity in the digital era, MSMEs must be able to implement digital technology through the use of communication tools such as computers, cellphones and iPads, providing internet networks to access various types of MSME product marketing information through websites, managing digital marketing tools such as the most widely used social media today (Tiktok, Instagram, Facebook and other social media as well as the use of the most widely used marketplaces such as Shopee, Tokopedia, Blibli and Lazada and SEO (Search Engine Optimization) without leaving digital ethics in using internet technology and privacy and security in using technology so that residents around Sukasetia Village can utilize digital marketing technology properly so that they can improve product quality and sales volume of the businesses they create can grow more rapidly because of this digital marketing technology.